Pengaruh Model Pembelajaran Inquiry Training Berbantuan Multimedia Terhadap Penguasaan Konsep Fisika Peserta Didik - Wildan Hidayat; Muhammad Taufik; Gunawan Gunawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
This research aim to examine the effect of multimedia assisted inquiry training learning model for students physic concept mastery. This type of research is quasi experiment with non-equivalent control group design. The research population was all students of XI MIA MAN 2 Mataram with a purposive sampling technique. The XI MIA 4 class was chosen as the experimental class and the XI MIA 3 class as the control class. hypothesis testing using independent t-test with 5% of significance level. Hypothesis testing yielded the concept mastery t count is 3.20 higher than the t table which has a value of 1.99. Based on the provisions, Ho is rejected and it is concluded that there are differences in mastery of physics concepts due to the practice of multimedia assisted inquiry training learning model. It means that there is a better increase of concepts mastery in the experimental class than the control class. This result can be proved by the N-gain test, where there is an increase of 53.92% in the medium category for concept mastery in the experimental class greater than the control class with an increase of 41.92% in the medium category.